Efektivitas Media Pembelejaran Visual Berbasis Lingkungan Di SMA Unggulan BPPT Darussholah - Firda Shahira; I Ketut Mahardika; Subiki Subiki; Putri Wihatma Andianti; Adisty Pyrenia (Jurnal Penelitian Pendidikan Fisika, 2022)
This research was conducted in one of the senior high schools in Jember Regency, namely BPPT Darussholah Superior High School with a total of 21 students in class XI. This research method uses a survey method by filling out questionnaires to determine the interest in learning and the level of understanding of students regarding the learning media that is demonstrated together, namely hydraulic jacks. From the research conducted, it was found that students preferred learning by using media or teaching aids. This also increases students' understanding of the material presented, because students not only receive an explanation of the material but students can also practice directly so that they better understand the material presented. This is known based on the answers to the questionnaire given to students.